Improving Electrical Conductivity, Thermal Stability, and Solubility of Polyaniline-Polypyrrole Nanocomposite by Doping with Anionic Spherical Polyelectrolyte Brushes - Su, Na (Nanoscale Res Lett, 2015)
The extent to which anionic spherical polyelectrolyte brushes (ASPB) as dopant improved the performance of polyaniline-polypyrrole (PANI-PPy) nanocomposite was investigated. Different characterization and analytical methods including Fourier transform infrared spectroscopy (FTIR), thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM), and X-ray diffraction (XRD) confirmed that ASPB serving as dopant could improve the comprehensive properties of PANI-PPy nanocomposite. It was different from dopants such as SiO(2), poly(sodium-p-styrenesulfonate) (PSS), and canonic spherical polyelectrolyte brushes (CSPB) which only enhanced the performance of PANI-PPy nanocomposite on one or two sides. The electrical conductivity of (PANI-PPy)/ASPB nanocomposite at room temperature was 8.3 S/cm, which was higher than that of PANI-PPy (2.1 S/cm), (PANI-PPy)/PSS (6.8 S/cm), (PANI-PPy)/SiO(2) (7.2 S/cm), and (PANI-PPy)/CSPB (2.2 S/cm). Meanwhile, (PANI-PPy)/ASPB nanocomposite possessed enhanced thermal stability and good solubility. In addition, the effects of polymerization temperature, the molecular weight of grafted polyelectrolyte brushes, and storage time on electrical conductivity were discussed.